2010
DOI: 10.1007/s00572-010-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi from Pecteilis susannae (L.) Rafin (Orchidaceae), a threatened terrestrial orchid in Thailand

Abstract: Eight endophytic fungi were isolated from roots of the threatened terrestrial orchid, Pecteilis susannae (L.) Rafin. Phylogenetic analysis based on an alignment of internal transcribed spacer regions of nuclear rDNA indicated that seven isolates belonged to the genus Epulorhiza and one to Fusarium. All fungal isolates were cultured with orchid seeds collected from three field sites near Doi Suthep-Pui National Park, Chiang Mai, Thailand. Seed germination and protocorm development were evaluated up to 70 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Fungal isolates CMU-Aug 007, CMU-Aug 013, CMU-Aug 028, CMU-AU 211 and CMU-AU 212 were isolated as described previously (Chutima et al 2011). The remaining fungai were isolated using a modified procedure of Zhu et al (2008).…”
Section: Isolation Of Mycorrhizal Fungimentioning
confidence: 99%
See 4 more Smart Citations
“…Fungal isolates CMU-Aug 007, CMU-Aug 013, CMU-Aug 028, CMU-AU 211 and CMU-AU 212 were isolated as described previously (Chutima et al 2011). The remaining fungai were isolated using a modified procedure of Zhu et al (2008).…”
Section: Isolation Of Mycorrhizal Fungimentioning
confidence: 99%
“…Except for the Epulorhiza isolates CMU-Aug 007, CMUAug 013 and CMU-Aug 028 were selected from our previous study (Chutima et al 2011), the fungal isolates were first identified using morphological characteristics and keys described in Barnett and Hunter (1987), Currah and Zelmer (1992), Currah et al (1997), Robert (1999) and Athipunyakom et al (2004a). DNA required for sequencing the ITS regions was obtained from mycelium as described previously (Chutima et al 2011).…”
Section: Fungal Identificationmentioning
confidence: 99%
See 3 more Smart Citations